(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2020)
Health is the most important thing in human life. Lifestyles and diets that are not suitable for the increase in the prevalence of regenerative diseases such as diabetes mellitus. Diabetes mellitus is a chronic disease characterized by a lack of the hormone insulin produced by the pancreas to regulate the amount of sugar levels in the blood. People do not realize that banana peels (Musa acuminata) can be used to prevent diabetes. Banana peel (Musa acuminata) has abundant nutritional content, including carbohydrates, protein, potassium. Based on other research articles, banana peels also contain a number of active compounds to prevent diabetes, namely pectin (10-21%), lignin (6-12%), cellulose (7.6% -9.6%), and hemicellulose (6). , 4-9.4%). Therefore, researchers have innovated to process banana peel waste (Musa acuminata) into COKUPI (Banana Skin Cookies) as a health promotion in preventing diabetes mellitus. The purpose of this study was to determine the potential of banana peel waste (Musa acuminata) as a prevention of diabetes mellitus. The benefit of this research is as a community guide in the utilization of banana peel waste (Musa acuminata). The material used in this study included banana peel cookies, alloxan, and mice. This study used an experimental method, namely by using the same 25 mice were given alloxan and measured blood sugar levels. After being measured, the white mice (Mus musculus) did fast for 18 hours. COKUPI was given with different treatments, namely negative control, positive control, doses of 100g, 200g, and 300g for 15 days. The results of this study were Kepok banana peels (Musa acuminata) which were processed into effective cookies as an alternative to prevent diabetes mellitus.